2016
DOI: 10.4102/ajlm.v5i2.452
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance for point-of-care testing: Ethiopia’s experience

Abstract: No abstract available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This study was comparable with the study conducted in Nigeria between 2009 and 2011 [7]. Four rounds of pre-characterized plasma panels for HIV, sputum films for tuberculosis and blood films for malaria were distributed quarterly scores increased from 74% to 95% from the first round to the third round, but decreased in the fourth round for HIV PT and average scores increased from 42% in the first round to 78% in the second round; but a decrease to 34% was observed in the fourth round for Tuberculosis PT while Malaria PT performance was 2% at first, but average scores increased between the second and fourth rounds, culminating in a fourth-round score of 39% which showed low performance compared to the study conducted on quality assurance for point of care testing among different heath facilities [11]. Many participants requested training and mentoring.…”
Section: Performance Ratementioning
confidence: 55%
“…This study was comparable with the study conducted in Nigeria between 2009 and 2011 [7]. Four rounds of pre-characterized plasma panels for HIV, sputum films for tuberculosis and blood films for malaria were distributed quarterly scores increased from 74% to 95% from the first round to the third round, but decreased in the fourth round for HIV PT and average scores increased from 42% in the first round to 78% in the second round; but a decrease to 34% was observed in the fourth round for Tuberculosis PT while Malaria PT performance was 2% at first, but average scores increased between the second and fourth rounds, culminating in a fourth-round score of 39% which showed low performance compared to the study conducted on quality assurance for point of care testing among different heath facilities [11]. Many participants requested training and mentoring.…”
Section: Performance Ratementioning
confidence: 55%
“…The WHO reported the underutilization of conventional VL platforms, with only a 36.5% capacity of the existing platforms being used in the reported countries (224). Similarly, other studies have reported underutilization of POC or near-POC instruments (222,225). Decentralized VL testing, if properly planned, offers several advantages, including (i) cost-efficient, flexible, and close monitoring of patients; (ii) faster turnaround times for patient results; and (iii) early detection of treatment failures for better patient management.…”
Section: Decentralization Of Vl Testingmentioning
confidence: 96%
“…Decentralized laboratories for VL testing would need to be supported by strong systems, including a sample referral network, an EQA program, human resources, a quality management system, a laboratory information system (LIS), and a supply chain. For example, Ethiopia has a decentralized laboratory network for VL determination and EID together with an effective specimen referral network to ensure that patient specimens are efficiently transported to viral testing laboratories (220)(221)(222).…”
Section: Decentralization Of Vl Testingmentioning
confidence: 99%
“…Coupled with the rapid scale-up of ART services in sub-Saharan Africa, the need for appropriate treatment response monitoring approaches had become indispensable [ 13 15 ]. However, it becomes evident that monitoring of treatment response remains the key challenge for program managers and policymakers in Ethiopia due to sub-optimal access to HIV VL testing for routine follow-up of treatment [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%